Cláusula penal no código civil - Keleti, Daniel de Leão (2007)
The penal clause institute study under the optics from historical development, by the light of the social alterations, on account of the strengthening of the negotiating table relations. The personal rights became the biggest responsible by the riches circulation in the contemporary society. Through the obligation study can be verified the relevant phenomenon of the business promotion. Because of this effervescence of the obligation as a way of riches circulation, the legal system has as challenge to concede legal security to these relations. The penal clause, exactly, looks for to strength the obligational link between the creditor and the debtor. At the same time it is a coercive force to the debtor to obey what he took upon as an obligation, as well as, it makes easy to the creditor the possibility of the indemnity pre fixation in case of not obey the obligation. Nevertheless the penal clause relevance to the obligation link strengthening cannot be made use as a way of subjection of the weaker part. The State desires the legal security, but, in the modern view never the human person dignity can be reached with the only justification of keeping an obligational link. In this pitch, must the State to interfere to adjust the penal clause to an equitable value